2022
DOI: 10.3390/membranes12050464
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing Extracellular Vesicles and Particles Derived from Skeletal Muscle Myoblasts and Myotubes and the Effect of Acute Contractile Activity

Abstract: Extracellular vesicles (EVs), released from all cells, are essential to cellular communication and contain biomolecular cargo that can affect recipient cell function. Studies on the effects of contractile activity (exercise) on EVs usually rely on plasma/serum-based assessments, which contain EVs from many different cells. To specifically characterize skeletal muscle–derived vesicles and the effect of acute contractile activity, we used an in vitro model where C2C12 mouse myoblasts were differentiated to form … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 76 publications
1
9
0
Order By: Relevance
“…The purpose of this study is threefold: (i) characterizing the electric fields; (ii) the influence of ES (AC) on liquid characteristics (DMEM); and (iii) influence of ES (AC) on the initial cell adhesion and calcium ion (Ca 2+ ) signaling of MG-63s. ES generated by IonOptix is described in studies with, e.g., myoblasts [ 46 ], or osteoblasts [ 12 , 14 ]. Ercan et al [ 12 ], showed a positive effect of IonOptix AC stimulation on osteoblast (hFOB 1.19) proliferation, but they technically modified the system with potentiometers to achieve a physiological current.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The purpose of this study is threefold: (i) characterizing the electric fields; (ii) the influence of ES (AC) on liquid characteristics (DMEM); and (iii) influence of ES (AC) on the initial cell adhesion and calcium ion (Ca 2+ ) signaling of MG-63s. ES generated by IonOptix is described in studies with, e.g., myoblasts [ 46 ], or osteoblasts [ 12 , 14 ]. Ercan et al [ 12 ], showed a positive effect of IonOptix AC stimulation on osteoblast (hFOB 1.19) proliferation, but they technically modified the system with potentiometers to achieve a physiological current.…”
Section: Discussionmentioning
confidence: 99%
“…The electric field is generated between two parallel graphite plates (i.e., a plate capacitor) 1.1 cm apart and in direct contact with the cells. We utilized a commercially available device from IonOptix (voltage controlled), which has been described earlier [ 12 , 14 , 46 ]. The IonOptix stimulator generates AC electric fields with constant biphasic rectangular pulses at a frequency of 7.9 or 20 Hz and voltage of 1 and 5 V, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to acknowledge that determining the proportion of SkM-derived EVs to total EVs in circulation poses several challenges. First, the presence of markers specific to the SkM origin, such as β- or α-sarcoglycans, integral components of the dystrophin-glycoprotein complex, cannot be guaranteed in all SkM-derived EVs [ 17 ], making it difficult to definitively confirm EVs originating from SkM contractile activity. Second, α-sarcoglycan has been detected not only in SkM but also in cardiac muscle [ 58 ].…”
Section: Myokines Exerkines and Extracellular Vesicles: Mining On The...mentioning
confidence: 99%
“…Second, α-sarcoglycan has been detected not only in SkM but also in cardiac muscle [ 58 ]. Third, intramuscular injections of fluorescently labeled EVs or genetic manipulation, which are excellent options in rodent models, are impractical in human studies [ 17 ]. Despite the difficulties in studying SkM-derived EVs in vivo, several in vitro studies have clearly demonstrated that both myoblasts and myotubes are capable of releasing EVs whose biological role in recipient cells is unclear [ 59 , 60 ].…”
Section: Myokines Exerkines and Extracellular Vesicles: Mining On The...mentioning
confidence: 99%
See 1 more Smart Citation